2021
DOI: 10.1002/ente.202100501
|View full text |Cite
|
Sign up to set email alerts
|

A Concise Review on Productivity and Economic Analysis of Auxiliary‐Component‐Assisted Solar Stills

Abstract: The supply of potable water is insufficient to meet the needs of the growing population and daily life. Due to high salt concentrations, ocean water cannot be used directly. Furthermore, the water in rivers and lakes is contaminated with industrial wastes, making it unsafe to drink. A solar still is a simple device that uses solar energy to purify saline water via evaporation and condensation. Solar stills have undergone various modifications to improve the daily productivity. Herein, an attempt is made to cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 115 publications
0
5
0
Order By: Relevance
“…To validate the performance of the enhanced solar still, the experimental results were compared with previously published measurements from Egypt and other countries, as shown in Table 7 (Dhivagar and Kannan 2022 ), (Dhivagar et al 2022b ), (Dhivagar 2021 ). The table demonstrates that the annual productivity of the modified solar still with NLF, BL, FSW, and SWP was approximately 9860, 11560, 12750, and 14960 l/m 2 , respectively.…”
Section: Comparison With Previous Publicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…To validate the performance of the enhanced solar still, the experimental results were compared with previously published measurements from Egypt and other countries, as shown in Table 7 (Dhivagar and Kannan 2022 ), (Dhivagar et al 2022b ), (Dhivagar 2021 ). The table demonstrates that the annual productivity of the modified solar still with NLF, BL, FSW, and SWP was approximately 9860, 11560, 12750, and 14960 l/m 2 , respectively.…”
Section: Comparison With Previous Publicationsmentioning
confidence: 99%
“…It was observed that the optimal number of fibers in the absorber basin improved the evaporation rate more effectively compared to a higher number of fibers. In future research, preheating systems could be employed to improve productivity and energy and exergy, depending on latent and sensible heating (Dhivagar 2021 ).…”
Section: Comparison With Previous Publicationsmentioning
confidence: 99%
“…A review of CPL produced by auxiliary components assisted solar desalination units and its productivity was discussed by Dhivagar. 62 The various auxiliary components such as evacuated tubes, flat plate collectors, heat pipes, biomass, gravel bed, heat pump, solar air, water heater were discussed. It was observed that the solar still operated by evacuated tubes had exponentially lesser heat losses than the flat plate collector.…”
Section: Vacuum Technology In Evacuated Tubesmentioning
confidence: 99%
“…Some of the research works were carried out in solar stills using a magnetic field to enhance the overall productivity 29–31 . Dumka et al 32 employed ring magnets in a solar still and boosted evaporation and productivity by 49.2% and 23.5% over CSS.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the research works were carried out in solar stills using a magnetic field to enhance the overall productivity. [29][30][31] Dumka et al 32 employed ring magnets in a solar still and boosted evaporation and productivity by 49.2% and 23.5% over CSS. It boosted convective heat transfer and productivity by 48% and 38%, respectively, according to Mehdizadeh Youshanlouei et al 33 To improve CSS productivity, energy, and exergy efficiency by 21.7%, 31.3%, and 22.6%, Dubey and Mishra 34 employed ring magnets and galvanized iron sheet metal.…”
Section: Introductionmentioning
confidence: 99%